Evolutionary and Functional Analysis of a Chara Plasma Membrane H+-ATPase - Zhang, Suyun; Habets, Myckel; Breuninger, Holger; Dolan, Liam; Offringa, Remko; van Duijn, Bert (Frontiers in Plant Science, 2020)
H+-ATPases are the main transporters in plant and fungal plasma membranes (PMs), comparable to the Na+/K+ ATPases in animal cells. At the molecular level, most studies on the PM H+-ATPases have been focused on land plants and fungi (yeast). The research of PM H+-ATPases in green algae falls far behind due to the lack of genetic information. Here we studied a potential PM H+-ATPase(CHA) from Chara braunii, a species of green algae belonging to the division Charophyta, members of which are considered to be one of the closest ancestors of land plants. The gene encodes a 107kDa protein with all 6 P-type ATPase-specific motifs and a long, diverse C-terminal domain. A new amino acid sequence motif R*****Q in transmembrane segment 5 was identified among the known PM H+-ATPases from Charophyta and Chlorophyta algae, which is different from the typical PM H+-ATPases in yeast or land plants. Complementation analysis in yeast showed that CHA could successfully reach the PM, and that proton pump activity was obtained when the last 77 up to 87 amino acids of the C-terminal domain were deleted. PM localization was confirmed in Arabidopsis protoplasts, however, deletion of more than 55 amino acids at the N-terminus or more than 98 amino acids at the C-terminus resulted in failure of CHA to reach the PM in yeast. These results suggest that an auto-inhibition domain is located in the C-terminal domain, and that CHA is likely to have a different regulation mechanism compared to the yeast and land plant PM H+-ATPases.